Pemberdayaan Masyarakat Terhadap Program Keaksaraan Fungsional di PKBM Daya - Indah Sari; Hamriani (Jurnal Berita Sosial, 2023)
Empowerment Through Functional Literacy Program So That People Understand More About The Basic Knowledge. Qualitative Research With A Sociological Approach, The Data Sources In This Study Are Primary Data Sources And Secondary Data Sources. Data Collection Methods Are By Observation, Interviews, And Documentation. Research Instruments Using Cameras, Notebooks, Cell Phones, And Interview Guides. After All The Data Is Collected, The Researcher Then Analyzes The Data With Data Reduction. Presentation Of Data (Data Display), And Drawing Conclusions (Drawing Conclusion). The Results Of This Study Indicate That The Implementation Of The Community Empowerment Process Through Functional Literacy Programs To Empower People Who Still Have Limited Basic Knowledge Or Are Illiterate, There Are Several Steps In The Implementation Of Empowerment Carried Out Including: Starting From Two Steps, Namely A.) This Program Is Divided Into Two Stages, Namely 1.) Direct Socialization Of The Functional Literacy Program Carried Out By Program Managers, 2.) Data Collection Of Prospective Learning Citizens Who Will Take Part In The Program And B.). Implementation Steps , Namely The Implementation Of Community Empowerment (Calistung Teaching Process (Read, Write, Count) To Residents Who Follow The Program). As Well As Inhibiting Factors In The Implementation Of The Functional Literacy Program At The Center For Learning Activities Of The Science Power Community, Namely: 1). Age Factor Which Causes A Decrease In The Function Of The Sense Of Sight Of Learning Residents Which Causes Them To Be Slow To Understand The Material Given By The Tutor, 2). Sight Factor 3.) Lack Of Motivation Of Citizens In Learning So That During The Process Of Receiving Learning Materials It Is Still Very Difficult For Residents To Understand The Program.